2004
DOI: 10.4049/jimmunol.172.1.123
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell TRAIL Eliminates Immature Dendritic Cells In Vivo and Limits Dendritic Cell Vaccination Efficacy

Abstract: Recent studies have implicated a possible role for NK cells in regulating dendritic cells (DC) in vitro. In the present study, we demonstrate that immature DC are rapidly eliminated by NK cells in vivo via a pathway dependent on the TNF-related apoptosis-inducing ligand (TRAIL). Elimination of NK cells and/or neutralization of TRAIL function during immunization with immature DC loaded with nonself or tumor Ags significantly enhanced T cell responses to these Ags and Ag-specific tumor immunity. These data sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
146
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 57 publications
6
146
0
1
Order By: Relevance
“…At a low NK:DC ratio (1:5), NK-DC interactions stimulate DC-mediated cytokine secretion (IL-12 and TNF-␣) and DC maturation. But, the converse NK-DC ratio (5:1) will result in killing of iDCs (38) through TRAIL-mediated apoptosis (45). iDC decrease, either by elimination or maturation, would increase Agpresentation efficiency by reducing nonresponsive DCs to the ongoing inflammation and thereby freeing up resources for reactive, maturing DCs.…”
Section: Discussionmentioning
confidence: 99%
“…At a low NK:DC ratio (1:5), NK-DC interactions stimulate DC-mediated cytokine secretion (IL-12 and TNF-␣) and DC maturation. But, the converse NK-DC ratio (5:1) will result in killing of iDCs (38) through TRAIL-mediated apoptosis (45). iDC decrease, either by elimination or maturation, would increase Agpresentation efficiency by reducing nonresponsive DCs to the ongoing inflammation and thereby freeing up resources for reactive, maturing DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL, also called APO-2L is a member of the tumor necrosis factor family that appears to induce apoptosis predominantly in transformed cells (Wiley et al, 1995;Sheridan et al, 1997), but also in some normal cells, for example stimulated splenocytes, memory or dendritic cells (Ursini- Siegel et al, 2002;Hayakawa et al, 2004;Janssen et al, 2005). Tumor necrosis factor-related apoptosis-inducing ligand induces apoptosis by binding to one of the two death domain-containing TRAIL receptors, that is DR4 (TRAIL receptor 1) and DR5 (TRAIL receptor 2) (Sheridan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NK cells regulate T cell responses through multiple direct and indirect mechanisms, including NK cell-mediated killing of activated CD8 + T cells (14,15,(18)(19)(20)(21), CD4 + T cells (18,19,22,23), and also of dendritic cells (DCs) (12,24,25). However, little is known about a possible NK cell-mediated inhibitory/regulatory role during antitumor immune responses.…”
mentioning
confidence: 99%